Maria Mies's Ecofeminist Thoughts on the Mandalika Project and Sasak Women - Fauzi Fauzi (Political Sciences Program Study, 2025)
This study discusses Maria Mies' ecofeminist perspective on the Mandalika project and its impact on the viability of Sasak women as entities living in the area. Ecofeminism in Mies' perspective is seen as an approach that connects women's equality and freedom with the phenomenon of exploitation of nature by capitalist companies. Maria Mies' ecofeminism gives rise to a subsistence perspective approach. The impact of this exploitation of nature affects women’s lives socially, economically, and health-wise. This study uses a qualitative approach with a library research data collection method. This study traces Mies' thoughts from her books and reviews the lives of Sasak women affected by the Mandalika Project. By using the ecofeminist approach in Mies' Subsistence perspective, this study concludes that Sasak women are in a condition of life that is not feasible in terms of health and economy due to the Mandalika project. Mies call this condition of Sasak women an unattainable step towards the goal of the subsistence perspective, the imaginary manipulation of capitalists, or the limited awareness of Sasak women to rise to fight for freedom and equality to live a decent life. Expectations drawn from this study can contribute to thinking about government policy and public awareness regarding the importance of paying attention to equality, justice, and the impact of the interconnectedness between nature, women, people, and a sustainable economy.